Lock Wall Deicing Studies. - Hanamoto,Ben (1977)
Four methods for removing the ice buildup on navigation lock walls on the Poe Locks at Sault Ste. Marie, Michigan, were investigated: mechanical pneumatic boots, high-pressure water jets, mechanical chain saws, and chemical coatings. Two of the more promising means of ice removal, the chain saw and the chemical coatings, are being developed further so that they may be used as operational aids for lock wall deicing during the winter navigation season. (Author)